Pension Fund Corporate Engagement: The Fifth Stage of Capitalism - Clark, Gordon; Hebb, Tessa (Relations industrielles / Industrial Relations, 2004)
Pension fund capitalism is a new, albeit evolving, stage of Anglo-American capital market development. It is marked by the ability of pension funds to aggregate the widely disbursed ownership of beneficiaries and therefore act as single entities with a unified voice. Pension funds within their investment portfolios are increasingly using this voice to engage companies. Such corporate engagement in its broadest definition is the use of one’s ownership position to influence company management decision making. Corporate engagement brings together four distinct underlying currents: first, the increased use of passive index funds; second, the corporate governance movement; third, the growing impact of socially responsible investing; and, finally, the impact of new global standards. At its best corporate engagement offers a long-term view of value that both promotes higher corporate, social and environmental standards and adds share value, thus providing long-term benefits to future pension beneficiaries.